Development of the Questionnaire of Motivations to disclose/ not disclose the non-genetic parenthood by gamete donation’s Questionnaire - Marques, Cristiana (2017)
Introduction: Parenting is a highly valued social role. However, for couples dealing with infertility this role can involve fertility treatments, and for some of them donor-assisted reproduction. For couples who use third party reproduction, another concern can emerge: tell the child about the donor conception, or preserve secrecy. Although arguments for decision-making have been studied, in Portugal research on this topic is scanty. Objectives: The current study sought out to develop the Motivations for Disclosing/Not Disclosing Non-genetic Parenthood through Gamete Donation (QMRDG), which is designed to assess motivations that influence the decision-making process of parents who use gamete donation regarding disclosure to his/her son/daughter his/her conception. Method: This exploratory study was conducted in a sample of 21 participants with age ranging from 30 to 49 years, who undergone third-party reproduction treatment and became parents. Participants completed a set of questionnaires through an online platform. Results: QMRDG revealed clear and comprehensible items. Data showed that most parents did not disclose to their child their donor conception due to the fact that the child is still very young, but their intention seems to be to disclose in the future. For parents who have disclosed, core motivations for that decision are based on the importance of honesty and on the right to know genetic origins. Concerning motivations for not disclosing the little importance given to genetics emerges as one of the most important ones.  Discussion: The QMRDG can be a promising tool in clinical practice and research with people who are pursuing fertility treatment with gamete donation. In this investigation parent’s tendency was to disclose to child donor conception.